Assessment of Combined Local Anesthesia and Ketamine for Pain, Swelling, and Trismus After Surgical Extraction of Third Molars - GARİP, HASAN (W B SAUNDERS CO-ELSEVIER INC, 2009)
Purpose: The aim of this study was to assess the clinical efficacy of combined treatment with local anesthetic and subanesthetic ketamine for the relief or prevention of postoperative pain, swelling, and trismus after the surgical extraction of third molars. Patients and Methods: Fifty patients undergoing the extraction of impacted mandibular third molars were included in the study. The patients were randomly divided into 2 groups: local anesthetic alone (LAA) and local anesthetic plus ketamine (LAK). The patients in the LAA group received 5 mL of a local anesthetic and saline combination comprising 2 mL of local anesthetic and 3 mL of saline. The patients in the LAK group received 5 mL of a local anesthetic, ketamine, and saline combination comprising 2 mL of local anesthetic and 0.3 mg/kg ketamine and saline. Results: Facial swelling on postoperative days was significantly lower in the LAK group than in the LAA group (P = .0001). The mouth opening on the postoperative days was significantly greater in the LAK group than in the LAA group (P = .0001). The pain scores on the VAS at 30 minutes and 1, 4, 12, and 24 hours after surgery were significantly higher in the LAA group than in the LAK group (P = .0001, P = .005). Conclusion: The combination of a local anesthetic and subanesthetic doses of ketamine during surgical extraction of third molars can produce good local anesthesia while affording a comfortable procedure for the surgeon and patient and providing good postoperative analgesia with less swelling and significantly less trismus. (C) 2009 American Association of Oral and Maxillofacial Surgeons J Oral Maxillofac Surg 67:1206-1210, 2009
Keywords: POSTOPERATIVE PAIN; SURGERY; METHYLPREDNISOLONE; INFILTRATION; TRAMADOL; EFFICACY; REMOVAL